What Is The Role Of Recruitment In Improving Employee Performance - Cendriyani, Yani (Journal of Management, 2024)
Employees are a company's most valuable resource when it comes to enhancing performance and achieving objectives. The purpose of this study is to ascertain how hiring and placement practices directly affect worker performance. The sample size in this study is made up entirely of PT employees. West Java's Ilham Jaya Farm Garut had 87 responders in all. Multiple linear regression analysis is the method used in this study. The study's findings demonstrate that factors related to hiring and placement have a favourable impact on workers' performance at PT. West Java's Ilham Jaya Farm in Garut